Research hotspots and trends of urology education in China and worldwide over the past decade - Yaxiong Tang; Yun Tan; Gang Chen; Cheng Ren (Medicine, 2026)
Background: To systematically compare the research landscape, thematic hotspots, and evolutionary trajectories of urology education in China and globally between 2015 and 2024, and provide evidence-based insights for optimizing urology residency training and clinical teaching reform. Methods: We searched for urology education papers published between 2015 and 2024 in Chinese databases (China National Knowledge Infrastructure (CNKI), Wanfang, VIP, Chinese dissertation database, National Urology Education Symposium proceedings) and international databases (Web of Science Core Collection, PubMed, ProQuest dissertation database, American Urological Association (AUA)/European Association of Urology ) annual meeting proceedings). Bibliometric methods were applied for keyword co-occurrence, cluster analysis, and burst detection using VOSviewer 1.6.19, CiteSpace 6.4.R1, and Bibliometrix 4.1.0. The validated Medical Education Research Study Quality Instrument (MERSQI) was used for quality control. Literature screening followed an adapted Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 statement. Results: We identified a total of 8217 records from all databases. After screening and quality evaluation, 1563 studies were finally included in the bibliometric analysis (1137 from China, 426 from other countries). Annual publication volume showed steady growth in both regions (average annual growth: 6.2% in China, 6.6% globally). Four core clusters were identified in Chinese studies: teaching methodology innovation, technology-assisted instruction, standardized residency training optimization, and professionalism cultivation, reflecting a practice-oriented problem-solving paradigm. Four clusters were identified in international studies: interprofessional education (IPE), continuing professional development. simulation training system construction, and nontechnical skills training, reflecting a theory-driven system-building paradigm. The mean MERSQI score was 6.2 for Chinese studies and 9.7 for international studies, indicating a substantial gap in methodological rigor. Conclusions: Urology education research has expanded rapidly worldwide over the past decade, with distinct developmental paths between China and Western countries. Future efforts in China should prioritize localized adaptation of educational technologies, construction of standardized specialty education systems, and improvement of research methodology to advance high-quality urology workforce development.